Embryogenic capability of cultivar IAS-5 of soybean - Mauro, Antonio Orlando Di; Oliveira, Roberto Carlos de; Oliveira, João Ademir de (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to study the genetic control of somatic embryo formation on cultivar IAS-5 of soybean. The experiment was carried out in a greenhouse, where four plants per pot were grown under a photoperiod of 14 hours at a temperature about 28°C. Several crosses between non-embryogenic parental lines (cultivars IAC-6, Paraná and IAC-15) and embryogenic parental line (cultivar IAS-5) and backcrosses to obtain F1, F2, RC1P1 and RC1P2 generations were performed. Immature cotyledons, with 4-6 mm in length, derived from parental lines and from F1, F2, RC1P1 and RC1P2 generations were grown for 90 days in Petri dishes containing the inductive N10 medium, in a growth chamber. The number of somatic embryos derived from induction was used to estimate genetic parameters. The results showed that somatic embryogenesis capability of cultivar IAS-5 is of quantitative nature and is controlled by twenty genes approximately.